DETERMINANT AUDIT FACTOR AND ACCEPTANCE OF GOING CONCERN OPINIONS - Wiranti, Adelia Putri; Amalia, Firda Ayu (COMPETITIVE, 2025)
This study aims to empirically test the effect of financial distress, auditor switching, and previous year's audit opinion on the receiving of going concern opinion. This study uses a purposive sampling technique with a sample size of 138 companies. Secondary data in the form of financial reports of property and real estate companies listed on the indonesia stock exchange in 2021-2022 are used as data sources. The data analysis technique is logistic regression. the results of this study indicate that the first hypothesis was rejected, with the variable financial distress having no effect on the variable of accepting the going concern audit opinion. the second hypothesis was rejected, with the auditor switching variable having no effect on the variable of accepting audit opinion going concern. the third hypothesis was accepted, with the previous year's audit opinion variable influencing the variable of receiving audit opinion going concern.